Influence of Synthetic Antiendotoxin Peptides on Lipopolysaccharide (LPS) Recognition and LPS-Induced Proinflammatory Cytokine Responses by Cells Expressing Membrane-Bound CD14 - Iwagaki, Akitaka (American Society for Microbiology, 2000)
Lipopolysaccharides (LPS) are proinflammatory bacterial products implicated in the pathogenesis of gram-negative sepsis and septic shock. Polymyxin B (PMB), a cyclic, cationic peptide antibiotic, inhibits biological activities of LPS through high-affinity binding to the lipid A moiety. Small synthetic peptides have been designed to mimic the primary and secondary structures of PMB to determine structural requirements for binding and detoxification of lipid A and to assess possible therapeutic potential. The purpose of this study was to compare and contrast the endotoxin-neutralizing activities of two synthetic antiendotoxin peptides (SAEP-2 and SAEP-4), PMB, and an LPS core-specific monoclonal antibody (MAb), WN1 222-5, based on their abilities to inhibit CD14-mediated target cell uptake of fluorescein isothiocyanate (FITC)-conjugated LPS, detected by flow cytometry and confocal microscopy, and LPS-induced production of the proinflammatory cytokines, interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-α), as measured by bioassays. PMB and SAEP-4 produced dose-dependent inhibition of FITC-LPS uptake by CD14-transfected Chinese hamster ovary fibroblasts (CHO-CD14 cells) and by human peripheral blood mononuclear cells. The anti-LPS MAb, WN1 222-5, also blocked LPS uptake by these cells and synergized with PMB and SAEP-4. LPS-induced IL-6 release was inhibited by PMB, SAEP-4, and MAb WN1 222-5, and these inhibitory activities were additive or synergistic. LPS-induced TNF-α release by PBMC was also inhibited by PMB and SAEP-4 alone and in combination with anti-LPS MAb. SAEP-2, in contrast, produced comparatively minor decrements in cellular uptake of LPS and LPS-induced cytokine responses, and did so only in the absence of serum, while a nonsense peptide exerted no discernible inhibitory effect on LPS uptake or LPS-induced cytokine expression in the presence or absence of serum. Thus, PMB and SAEP-4, like the LPS-reactive MAb, WN1 222-5, block proinflammatory activities of LPS in part by preventing LPS recognition by membrane-bound CD14-expressing target cells. Differences in peptide structure, however, like those exemplified by SAEP-2 and SAEP-4, may differentially affect the endotoxin-neutralizing potency of these peptides despite similar binding activity against lipid A, reflecting possible differences in peptide solubility or peptide regulation of intracellular signal transduction.